A Report on the Use of Open Access Podcasting in the Promotion of Social Work. Issue 1 (2nd January 2016) - Fronek, Patricia; Boddy, Jennifer; Chenoweth, Lesley; Clark, Julie
Abstract: Open access podcasting or podcasts on the internet on specific disciplinary topics are gaining prominence but are not well researched. This paper explores the usefulness of a new podcast series for social workers freely available on the internet that aims to: promote the profession of social work and contribute to a social work identity; make connections between theory, research, and practice; introduce students to real-life practice issues much earlier than often occurs in undergraduate degrees; and provide practitioners with opportunities for ongoing professional development. The evaluation was based on social media and website statistics, a survey of 22 students and nine educators, and a content analysis of listener feedback. While the evaluation provided limited evidence that all the aims had been met, the findings revealed very positive attitudes towards the initiative.